If we will start by solving for y, it means that x is substituted in one of the equations.
If we clear the value of x from the first equation and replace it in the second equation, we would get:
![\begin{gathered} x+3y=14 \\ x=-3y+14 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/v5d9m4tv1kgpsbd6wl8cxbyu2sb50tyq22.png)
![\begin{gathered} -5x+6y=-28 \\ -5(-3y+14)+6y=-28 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/608m1suu38hglyy67tqzklb2eebm8d5g56.png)
Option A does not correspond to an equation of the system as it would be:
![\begin{gathered} -3y+14=-6y-28 \\ x=-3y+14\longrightarrow x=-6y-28 \\ x+6y=-28 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/itfra2g8w1k0w5q0cw6shnfnto86u7606a.png)
It is ignoring the coefficient -5 that multiplies x in the second equation.
Option B is exactly the result we have obtained from the substitution, so this is the equation.
Option C has the sign wrong as x=-3y+14.
Option D does not substitute x, so it won't be the step to solve for y.
Answer: Option B.